2018
DOI: 10.5536/kjps.2018.45.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Organic Sulfur on Performance, Egg Quality and Cell-mediated Immune Response of Laying Hens

Abstract: This study aimed to evaluate the dietary effect of organic sulfur (OS) supplementation on performance, egg quality and serum constituents in laying hens. A total of 360 Lohmann brown laying hens at the age of 31 weeks were distributed into four treatments having five replicates of 18 hens each until 54 weeks. The hens were fed four levels (0.0, 0.1, 0.2 and 0.4%) of OS with basal diet. The number of eggs was investigated daily, and egg quality was confirmed every 8 weeks. Sulfur content in eggs, interleukin 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 18 publications
0
19
3
2
Order By: Relevance
“…In cardiac cells, MSM inhibits inflammatory responses by regulating TNF-α signaling [ 30 ]. Non-toxic sulfur (NTS) has been used in livestock feed to enhance immunity and meat quality, and studies have shown that oral administration of NTS in rats does not induce cell death [ 33 , 34 ]. NTS exhibits anti-inflammatory activity against human THP-1 cells [ 22 ] and enhances growth hormone signaling in mouse C2C12 cells [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cardiac cells, MSM inhibits inflammatory responses by regulating TNF-α signaling [ 30 ]. Non-toxic sulfur (NTS) has been used in livestock feed to enhance immunity and meat quality, and studies have shown that oral administration of NTS in rats does not induce cell death [ 33 , 34 ]. NTS exhibits anti-inflammatory activity against human THP-1 cells [ 22 ] and enhances growth hormone signaling in mouse C2C12 cells [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…To utilize mineral sulfur, various substances (boiled pine tree or black soybean extract) are mixed with precipitated mineral sulfur, centrifuged and dehydrated to remove harmful components (27). The addition of non-toxic sulfur (NTS) to livestock feed has been demonstrated to improve immunity and meat quality (28). In addition, repeated oral administration of NTS did not induce toxicity in rats (29).…”
Section: Introductionmentioning
confidence: 99%
“…The hens were fed four levels (0.0, 0.1, 0.2 and 0.4%) of OS with basal diet. The result of the study showed that egg production tended to increase with 0.4% OS in diet after 39 weeks of age and, there was a significant effect (P < 0.05) from 47 to 54 weeks of age (Chun et al, 2018). At physiological concentrations of I and Se, thyroid hormones play an important role in regulation the organism's resistance and productivity.…”
Section: Discussionmentioning
confidence: 93%